Quality Analysis Of Digital Business Services In Improving Customer Satisfaction - Diana Putri Lazirkha; Jane Hom; Vivi Melinda (Startupreneur Business Digital (SABDA Journal), 2022)
Consumption behavior is changing as the times change, particularly in the technology era. The background problem it is difficult to predict which items or services will be in high demand. The background of this research is number of shuttered stores, malls, and supermarkets demonstrates that the internet era creates a place for consumer democracy. Then there is only one way out, and that is marketing reform. E-commerce (online buying and selling) as research objects has emerged in Indonesia, with one example being Shopee, which is focused on mobile applications and websites. It began as a Singaporean e-commerce platform under the Sea Group in 2015 and has since grown to Malaysia, Thailand, Indonesia, Brazil, et cetera. This study was carried out in order to detect and evaluate consumer behavior in the digital era in order to enhance sales. To depict the buying behavior in genuine words, a qualitative technique was adopted as method. By posing a few random questions on online retail purchases to respondents. To see the symptoms, around 113 people were chosen based on specific criteria. The findings indicate that customers in this day and age are ready for an online shopping strategy. There are gaps in almost every indicator except the first statement indicator from the Compensation dimension The primary factor is convenience. The results shows that convenience refers to marketing characteristics such as novelty like being able to do it anywhere, saving time and money, reduced rates, flexible payment options, and friendlier service.